2023
DOI: 10.21203/rs.3.rs-3160213/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microcomputed tomographic evaluation of 6 NiTi files on the pericervical dentin and the smallest dentin thickness zones in mesial root canals of mandibular molars: An in vitro study

Abstract: Objectives: The aim of this study was to evaluate six files on the pericervical dentin (PCD) and the smallest dentin thickness zones (SDTZ) in mesial root canals of mandibular molars. Materials and Methods: Sixty mesial roots with 2 canals were scanned before and after instrumentation with WaveOne Gold (WG), Reciproc Blue (RB), TRUShape (TS), XP-endo Shaper (XP), iRace (IR), and TruNatomy (TN). Surface, volume, structure thickness, SMI, and centroids were evaluated at the PCD, and the changes in the SDTZ were … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The changes in root canal surface area and canal volume after preparation with both VB and TN groups were similar with no signi cant differences. TruNatomy showed no signi cant differences in the changes in canal area after instrumentation when compared to Vortex Blue, ProTaper Next, XP-Shaper [5,19,24]. Although signi cantly less changes in canal surface area were observed when TruNatomy was compared to WaveOne Gold, Reciproc Blue, TRUShape and iRace [19].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The changes in root canal surface area and canal volume after preparation with both VB and TN groups were similar with no signi cant differences. TruNatomy showed no signi cant differences in the changes in canal area after instrumentation when compared to Vortex Blue, ProTaper Next, XP-Shaper [5,19,24]. Although signi cantly less changes in canal surface area were observed when TruNatomy was compared to WaveOne Gold, Reciproc Blue, TRUShape and iRace [19].…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, Vortex Blue les resulted in 55-58% of untouched canal surface area with a signi cant higher percentage when compared to XP-Shaper and TRUShape [21][22][23]. The previous studies showed higher percentage of untreated canal walls [19,20].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations